The role of social media ın real estate marketing: A research on the transformation of real estate marketing in turkey - Aytekin, Çiğdem; Keskin Demirli, Seray Merve (My University, 2017)
While the new media changes our daily life practices, it also causes some transformations in the field of marketing. Today it can be said that the real estate sector is also inevitably affected by this transformation and that it has developed new business models that include social media. Alexa is a website managed by amazon.com, which displays web traffic on a world and country basis. In this way, businesses can continuously monitor the visitor performance of their websites. In this study, the rankings of the Alexa web site were used to construct the sample of the research and in this way the visitor traffic was determined by the highest five real estate website in Turkey tracing techniques. On the other hand, the practices of real estate web sites to use social networks have been compared to the Alexa value ranks by examining them on specific networks and within defined metrics. Thus, it can be shown whether the real estate web site with the highest value metric has the same order in the Alexa valuation, and the role of social media in real estate marketing is evaluated within the dimensions of transformation. Research is essential since it makes an instantaneous evaluation of the circumstances and snaps a moment in the timeline.
Keywords: Social Media,Transformation